Performance of Fish Farms in Vietnam–Does Financial Access Help Improve Their Cost Efficiency? - Thanh Ngo; Hung V. Vu; Huong Ho; Thuy T. T. Dao; Hai T. H. Nguyen (International Journal of Financial Studies, 2019)
For a common small- to medium-sized fish farm in an agricultural-based economy, monitoring costs is very important, since financial constraints are always a problem for these farmers. This will be thus easier if the farmers can get access to external funds. This paper used data envelopment analysis (DEA) to examine the technical efficiency, cost efficiency and allocative efficiency of 639 fish farms in the Red River Delta (RRD) in Vietnam in 2018 to see how fish farmers control their costs and if financial access can really help in this matter. We found that these fish farms were very inefficient, meaning that they did not succeed in monitoring and allocating their costs and resources. Among the factors that could improve their efficiency, we found that developing the rural banking system to provide more financial access for RRD fish farms is an important solution.